CENTRAL CAUCASASIA” INSTEAD OF “CENTRAL EURASIA - Papava, Vladimer (CENTRAL ASIA AND THE CAUCASUS, 2008)
The Soviet Union’s disintegration not only gave rise to new independent states, a process of historic importance, it also began their integration into new geopolitical areas. Their geographic outlines visible under Soviet power were confirmed by the Soviet Union’s economic structure. Latvia, Lithuania, and Estonia together were called “Pribaltika;” Azerbaijan, Georgia, and Armenia were known as the Trans-Caucasus while Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan together formed “Sredniaia Azia” (Middle Asia). There were also corresponding economic regions of the U.S.S.R. In some cases, Kazakhstan was viewed as part of “Sredniaia Azia,” but it was normal practice to discuss the Kazakh economic region separately because of its relatively large size.It comes as no surprise that the independence and sovereignty of these states raised the question of finding new names for these geopolitical areas to emphasize their newly acquired independence from Moscow. In fact, certain publications (mainly by Russian authors) are still using the names inherited from imperial times. Latvia, Lithuania, and Estonia have deemed it necessary to drop the term “Pribaltika” as a “Soviet holdover” in favor of the current “Baltic countries.” Today, the terms “Southern Caucasus” and “Central Asia” (which includes Kazakhstan) have essentially ousted the old terms “Trans-Caucasus” and “Sredniaia Azia” (Middle Asia).Recently the relatively new geopolitical term “Central Eurasia” had been gaining currency. It is normally applied to Azerbaijan, Armenia, Georgia, Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan, which are treated as a single geopolitical area. I am convinced that this is not completely correct from the geopolitical viewpoint since it still reflects the Russian idea of this geopolitical expanse.Here I have posed myself the task of revising some of the issues related to the region’s geopolitical content from the position of a descriptive approach, that is, irrespective of the aims the world or regional powers are…………